HUBUNGAN DUKUNGAN KELUARGA DAN SELF ESTEEM DENGAN RESILIENSI DIRI LANSIA HIPERTENSI DI KELURAHAN GROGOL - Nabila Nasya (2023)
Hypertension can cause various changes in various aspects, ranging from physical, psychological, and social. Therefore, high resilience is needed so that individuals who experience hypertension are able to survive and minimize feelings of discomfort from changes that occur that have an impact on quality of life. This study was to determine the relationship between family support and self-esteem with the self-resilience of hypertensive elderly people. Observational analytic method through a cross sectional approach with data analysis using the chi square test, as well as quota sampling technique to take a sample of 150 respondents used in this study. PSS-Fa, RSES, and CD-RISC questionnaires were used for data collection. The results of the study found a relationship between family support and self-resilience (p value = 0.000) and found a relationship between self-esteem and self-resilience (p value = 0.000). It can be concluded that good family support and high self-esteem are essential factors of self-resilience in the elderly with hypertension so that they are able to adapt to change. So that the elderly with hypertension can increase self-esteem through self-loving attitudes, and reduce the attitude of giving up easily. In addition, families can increase support by providing encouragement, preparing and reminding them of medication consumption, and arranging food menus. In this study, researchers experienced obstacles in the research licensing process, data collection, and the discussion process due to a lack of references.